Pengawasan dan Penegakan Hukum Terhadap Bisnis Digital (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research explores the supervision and law enforcement concerning digital businesses. The rapid growth of digital businesses has significantly impacted the global economy, while simultaneously posing various legal challenges. This study aims to analyze the role and effectiveness of supervision and law enforcement on digital business actors in ensuring compliance with applicable regulations. The research methodology employs a qualitative approach, involving literature review, analysis of relevant legal regulations, and case studies on the implementation of supervision and law enforcement on digital businesses in various countries. The findings highlight the legal challenges faced by governments and supervisory bodies in coping with the developments in the digital business landscape. The study also evaluates various strategies that can be employed to enhance the effectiveness of supervision and law enforcement on digital businesses, including cross-sectoral collaboration, the utilization of information technology, and the development of regulations that are responsive to the dynamics of digital businesses. The implications of the research findings are expected to provide a more comprehensive insight into addressing the legal challenges emerging alongside the evolution of digital businesses in the era of globalization.